Investigation Of Mechanical Properties On Cement Paste Filled With Palm Oil Fuel Ash (POFA) - Suhaimi, Muhamad Syirazi (2019)
Investigation on impact strength and compressive strength attribute of cement paste filled with palm oil fuel ash (POFA) based pozzalonic composites was performed in this research. In order to preserve the environment for future sustainability, the idea of mixing natural waste material in their original form is something that could be a brilliant idea for designing a sustainable based product innovation. Thus, POFA been added into cement paste rather than by just mixing of only cement with water and sand to create concrete, could be the smart way to establish an improvement for both impact and compressive strength of the resulted cured cement. The main objectives of this study are to evaluate the effect of curing days and amount of POFA added into the composite mixture and examine their resulted impact strength and compressive strength of produced specimen. A combination of mixing cement with varied percentages of POFA (0%, 10%, 20% and 30% by wt %) and sand into cement portion (2:3 ratio) and fixed amount of water content of 0.4 were carried out in order to determine the impact strength and compressive strength for the pozzalonic composites. This has applied different number of curing days of 7, 14, 21 and 28 days of curing periods in order to determine the most optimum parameter of curing duration since curing day’s gives prominent effects to the mechanical properties of prepared samples. Also, this research investigated the correlation between strength with resulted composites microstructure by using the Scanning Electron Microscope (SEM). In addition, the Rockwell Hardness test, water absorption test and density test also conducted to investigate the physical state of cement paste composites filled with POFA. From this study, C/POFA 1 (90/10 wt. % of cement/POFA) composite with prolonged curing duration leads into significant improvement of resulted mechanical properties of produced composites. The use of POFA as a cementitious material could replace small amount of cement paste utilization that absolutely can help on preserving concrete mineral resource, lowering cement paste cost and last but not least, provide another candidate of advanced materials derived from natural waste.